PERLINDUNGAN HUKUM TERHADAP PEMEGANG DESAIN INDUSTRI BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2000 - Yunanda Sukma (JOURNAL OF LAW AND NATION, 2024)
Industrial Design is one of the intellectual property rights regimes regulated in Indonesian laws and regulations. The research method used in analyzing and researching this case study is through a normative juridical method with the main data in the form of secondary data obtained by literature study and analysis of legislation relating to Industrial Design. Application of novelty in industrial design based on Law no. 31 of 2000 is very important, because this protection can protect works resulting from creativity and imagination so that they are protected from violations of industrial designs by other designers for irresponsible things, and also by registering and protecting new designs. The industry will receive industrial design rights, with these industrial design rights the designer can carry out activities within the scope of industrial design. Because basically the value of novelty is very important and an industrial design that can be protected and registered must have novelty value, which means that a registered design has never existed and has never been registered before. A novelty value is also assessed based on the design having never been circulated to the general public, either through print media, social media or electronic media. And Exclusive Rights are the Right to exercise the Industrial Design Rights that one has and to prohibit other people from making, using, selling, importing, exporting, and/or distributing goods that are granted Industrial Design Rights without their consent.